Cell Mapping for Nanohybrid Circuit Architecture Using Genetic Algorithm - 储著飞 夏银水 王伦耀 (Journal of computer science and technology, 2012)
Nanoelectronics constructed by nanoscale devices seems promising for the advanced development of integrated circuits （ICs）. However, the lack of computer aided design （CAD） tools seriously hinders its development and applications. To investigate the cell mapping task in CAD flow, we present a genetic algorithm （GA） based method for Cmos/nanowire/MOLecular hybrid （CMOL）, which is a nanohybrid circuit architecture. By designing several crossover operators and analyzing their performance, an efficient crossover operator is proposed. Combining a mutation operator, a GA based algorithm is presented and tested on the International Symposium on Circuits and Systems （ISCAS） benchmarks. The results show that the proposed method not only can obtain better area utilization and smaller delay, but also can handle larger benchmarks with CPU time improvement compared with the published methods.